PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DIREKTORAT JENDERAL PERHUBUNGAN DARAT KEMENTERIAN PERHUBUNGAN - Hendriyaldi Hendriyaldi (Universitas Batanghari Jambi, 2017)
In the current era of globalization, requires improving the quality of human resources, in particular for government officials in providing services to the public. Many attempts were made by the government and the community to improve the situation. But the performance of the civil service is still cause for concern. Well as civil servants, motivation and discipline are the factors that important role in achieving business goals of an organization. This study aims to determine partially the effect of motivation and discipline on the performance and simultaneously the influence of motivation and discipline on the performance of the Directorate General of Land Transportation Ministry of Transportation. The independent variables are motivation and discipline, the dependent variable is the performance. The research method uses quantitative research. Data collection techniques using a questionnaire based on Likert scale. The sampling method is done randomly. This study population of 60 people and all of the population being sampled (saturated sample). The analytical method used is multiple linear regression. Based on the analysis it can be concluded there is a significant and positive impact partially between motivation on the performance, and there is a positive and significant effect partially between discipline on performance. F Test results support the hypothesis that motivation and discipline simultaneous effect on the performance by 72.3 percent. Other factors that can affect the performance that not yet be studied in this research , recommended for further research.Keywords: motivation, discipline, employees’ performance